Enhancing the mechanical properties of natural jute yarn suitable for structural applications. (12th May 2021) - Ashadujjaman, Md.; Saifullah, Abu; Shah, Darshill U; Zhang, Minglonghai; Akonda, Mahmudul; Karim, Nazmul; Sarker, Forkan
Abstract: Manufacturing natural-based high-performance composites are becoming of greater interest to the composite manufacturers and to their end-users due to their bio-degradability, low cost and availability. Yarn based textile architecture is commonly used in manufacturing these composites due to their excellent formability. However, for using natural based yarn as a reinforcing architecture in high load-bearing structural composite applications, a significant improvement in mechanical performance is required. Particularly, jute fibre yarn suffers from poor mechanical properties due to the presence of a fibrillar network, polysaccharides and other impurities in the fibre. For achieving this, we use aqueous glycine treatment (10%, W/V) on alkali(0.5 %, W/V) and untreated jute yarns for the first time. The glycine treatment on alkali-treated jute yarns (ATG) shows a huge improvement in tensile strength and strain values by almost ∼105% and ∼50 % respectively compared to untreated jute yarns (UT) because of the strong interactions and bonds developed between glycine, alkali and jute yarns. It is believed that the newly developed glycine treated jute yarns will be helpful to promote jute yarns in composite industries where load-bearing is the primary requirement and replace their synthetic counterparts.